Methodological foundations for compiling a list of critical mineral resources - S. S. Salmanov (Известия высших учебных заведений: Геология и разведка, 2024)
Background. Scientific and technological progress, along with the development of high technologies, leads to a rapid increase in the variety of mineral resources used in strategically important sectors of the national economy. The growing significance of certain minerals for national security and the monopolization of the high-tech raw materials market encourage governments and the scientific community to develop concepts for ensuring national economies with critical mineral resources.   Aim. To clarify the terminology related to strategic, scarce, and critical mineral resources, to establish criteria for classifying various types of mineral resources as critical, and to create an original list of critical mineral resources.   Methods and materials. In order to achieve this aim, a comprehensive set of general and specific research methods was employed, including comparative analysis and synthesis, systematization and generalization, grouping, induction, and deduction.   Results. The study involved analyzing definitions of strategic, scarce, and critical mineral resources used in both Russian and international practices. The need for introducing the category of critical mineral resources was substantiated to establish priorities in the strategic planning of the development of the country’s mineral resource base. Criteria for classifying certain types of mineral raw materials as critical have been developed and an original list of critical mineral resources has been compiled.   Conclusion. The analysis of critical mineral resources listed by the author revealed that Russia possesses significant reserves and resources of most of these resources, and in some cases holds leading positions. A prerequisite for ensuring national economic security comprises the accelerated development of its own mineral resource base of critical mineral resources and the elaboration of innovative technologies for processing mineral raw materials. Anti-crisis state management can provide the necessary impetus in the given direction by mobilizing production, financial, human, scientific, and entrepreneurial resources.